2016
DOI: 10.1097/fch.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Sociocultural Determinants in an Asian Indian Community

Abstract: In a US population of adult male and female Sikh immigrant participants (N = 350), we explored sociocultural factors related to depression, giving participants a choice between English or Punjabi surveys. Language preference pointed to a subgroup with higher levels of depression and lower satisfaction with life. Underreporting of depression suggests a general reluctance to discuss depression. While multiple sociocultural variables were associated with depression bivariably, multivariate analysis identified neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Religious beliefs and social expectations, including those governing family and community relationships, are factors that may influence AI immigrants daily living, interpretation of new experiences, and health outcomes [ 23 ]. As reported previously [ 21 ], we found that while overall reporting of mental health issues was low, depression was significant among women in the Punjabi community. As this was an exploratory study we had not preselected any subgroups, rather explored patterns within the Punjabi community as a whole.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Religious beliefs and social expectations, including those governing family and community relationships, are factors that may influence AI immigrants daily living, interpretation of new experiences, and health outcomes [ 23 ]. As reported previously [ 21 ], we found that while overall reporting of mental health issues was low, depression was significant among women in the Punjabi community. As this was an exploratory study we had not preselected any subgroups, rather explored patterns within the Punjabi community as a whole.…”
Section: Introductionsupporting
confidence: 84%
“…On average, women were significantly younger than men at the time of marriage, had been married a shorter amount of time, were less likely to be employed, and more likely to have been born in India. As noted in our previous work [ 21 ], the mental health variables were significantly different between genders; on average, women indicating elevated levels of anxiety and depression while men indicated levels within the normal range. Therefore, in the current study we first explored participants by survey language preference within gender groups.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…It is worth noting that all drivers in our study were men born outside Canada. Gender and ethnocultural factors may contribute to underreporting experiences of mental health issues, particularly among South Asians (Roberts et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Third, value-based barriers may emerge due to the fact that traditional psychotherapy in the United States is not in line with the collectivist value commonly held by Asian-Americans. There is a strong hesitation to discussing mental health issues among Indian immigrants (Roberts, Mann, & Montgomery, 2016). The collectivist or interdependent groups value collaboration and connection in a way that is different than the majority group, which is much more focused on individualism as a feature of healthy identity development (Leong & Lou, 2001;Markus & Kitamaya, 2001).…”
Section: Barriers To Treatmentmentioning
confidence: 99%